Management of Acute Mesenteric Ischemia: A Critical Review and Treatment Algorithm. (April 2016) - Zhao, Yang; Yin, Henghui; Yao, Chen; Deng, Jiong; Wang, Mian; Li, Zilun; Chang, Guangqi
Background: Acute mesenteric ischemia (AMI) due to a sudden loss or decrease in blood perfusion to the mesentery represents a highly lethal condition. However, the optimal surgical management remains debatable and merits a more clear recommendation based on a higher level of evidence. Methods: A systematic review of articles published between 2000 and 2013 was performed. Patients were divided into endovascular treatment (ET), open surgery (OS), and hybrid technique (HT) groups. Data of patients' demographics, procedural information, clinical outcomes including mortality, morbidity, primary patency rate, technique success, primary intestinal resection rate, and second-look laparotomy rate, and follow-up were all retrieved. Comparison between the ET and the OS groups was made using 2-sided Student t test and 2-sided χ 2 test or Fisher exact test where appropriate. Results: Twenty-eight articles with a total of 1110 patients were included for the review. The ET group had lower in-hospital mortality and morbidity but similar survival rate during follow-up compared to the OS group. The primary patency rate was higher in the ET group. The overall bowel resection rate was lower in the ET group, and nearly every patient in the cohort who required second-look laparotomy required bowel resection. The HT group seemed to have the lowest mortality and acceptable second-look laparotomy rate and morbidity. Comparison between the HT group and other groups was not possible due to the limited number of cases available for review. Conclusion: Endovascular treatment may serve as a first-line therapy for select patients when there is a low suspicion for intestinal necrosis. Open surgery should be reserved for emergency conditions requiring exploratory laparotomy. Hybrid technique may be an especially effective approach for treating AMI, with low morbidity and mortality, although further studies are required comparing it to OS and ET.